ANALISIS PENGARUH STRESSOR PERAN TERHADAP TURNOVER INTENTION MELALUI KEPUASAN KERJA (Studi Pada Perawat RS. Panti Wilasa Citarum Semarang) - Adika Widianto, Jonathan; Perdhana, Mirwan Surya (Diponegoro Journal of Management, 2018)
Basically nursing is recognized as one of the jobs that are full of pressure, so in this case work stress becomes one of the important issues that need to be considered among nurses. Stress on the nurses is caused by several factors derived from the role stressor. This study aims to analyze the effect of some kind of role stressors on turnover intention through job satisfaction among nurses. It was conducted on 146 nurses at the hospital at the Panti Wilasa Citarum Â Semarang hospital. Analysis of structural equation model (SEM) was used to identify and explain the result from the relationship between each role stressors variable towards job satisfaction and turnover intention variable. All variables in this study were measured using 29 indicators.The result of this study indicate that role stressors variableÂ  such as role ambiguity, role conflict, role overload, and work-family conflict are found to have a direct negative effect on nurse job satisfaction. But relationship between role ambiguity and role conflict variable are both statistically found to have an insignificant negative effect on job satisfaction variable. Job satisfaction was found to have a significant negative effect on turnover intention variable.